1977
DOI: 10.1099/00221287-99-2-325
|View full text |Cite
|
Sign up to set email alerts
|

Transfer and Expression of Pseudomonas Plasmid RP1 in Caulobacter

Abstract: SUMMARYThis study demonstrates that the host range of Pseudomonas plasmid RPI includes the genus Caulobacter. Caulobacter was shown to acquire three antibiotic resistance markers located in RPI. A fourth plasmid marker, susceptibility to an RNA bacteriophage, was not expressed, but could be transferred from Caulobacter to Escherichia coli. The lack of phenotypic expression of the phage marker was manifested by the inability of the phage to adsorb or to produce plaques on Caulobacter transcipients.Matings of Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…Previous reports of recombination in Caulobacter (10,11,15) have described procedures that require heavy mutagenesis to confer donor ability, an aspect that makes donor isolation laborious and renders the isolates of questionable value for genetic analysis by virtue of the multiple mutations introduced during this type of treatment (8). These problems have been obviated by the demonstration that promiscuous drug resistance factors, such as RP4, transfer conjugally from Escherichia coli to C. crescentus at a high frequency and promote significant chromosomal mobilization in C. crescentus (1,5). Inc P-1 R-factors enabled the rapid construction of linkage maps for several gram-negative bacteria for which no native fertility factor was available (3,4,12,13,21,22).…”
mentioning
confidence: 99%
“…Previous reports of recombination in Caulobacter (10,11,15) have described procedures that require heavy mutagenesis to confer donor ability, an aspect that makes donor isolation laborious and renders the isolates of questionable value for genetic analysis by virtue of the multiple mutations introduced during this type of treatment (8). These problems have been obviated by the demonstration that promiscuous drug resistance factors, such as RP4, transfer conjugally from Escherichia coli to C. crescentus at a high frequency and promote significant chromosomal mobilization in C. crescentus (1,5). Inc P-1 R-factors enabled the rapid construction of linkage maps for several gram-negative bacteria for which no native fertility factor was available (3,4,12,13,21,22).…”
mentioning
confidence: 99%
“…However, certain fundamental questions still remain unanswered, such as the role of the swarmer and stalked cell types in this process. Alexander & Jollick (1977) found that stalked and not swarmer bacteria were recipients in plasmid transfer in C. vibrioides. Since preliminary results obtained in our laboratory (Markiewicz & Kwiatkowski, 1980) point to the involvement of ATP-dependent deoxyribonuclease activity in conjugational transfer in Caulobacter, differences in the activity of this nuclease in the two cell types may reflect the unequal role of these cells in this process.…”
Section: Resultsmentioning
confidence: 95%
“…Changes in the pattern of DNA-binding proteins during the cell cycle (Cheung & Newton, 1977;Z. Markiewicz, unpublished results) as well as the finding that stalked and not swarmer bacteria are recipients in plasmid transfer in Caulobacter vibrioides (Alexander & Jollick, 1977) led me to expect changes in the activity of this deoxyribonuclease in the separate cell types of C. crescentus.…”
Section: Introductionmentioning
confidence: 99%
“…Alexander & Jollick (1977) demonstrated the transfer of plasmid RP1 to Caulobacter crescentus WS 12 and Caulobacter vibrioides CV6. Ely (1 979) subsequently transferred plasmids RP4, RK2, R702, R68.45 and R46 to several auxotrophic derivatives of C. crescentus C B 1 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In their study of R P l expression in Caulobacter, Alexander & Jollick (1977) found that although the Caulobacter R+ strains expressed the three R P 1 -specified antibiotic resistance markers (kanamycin, tetracycline and carbenicillin), these strains did not become susceptible to the plasmid-dependent phages P R D l or PRRl (as determined by a spot test using high titre phage lysates or by plaque formation using lower titre phage suspensions). In contrast, the RP4-containing Caulobacter strains of Ely (1 979) were susceptible to high titres of those phages by the spot test but neither PRD 1 nor PRR 1 formed plaques on his strains.…”
Section: Introductionmentioning
confidence: 99%